Theoretical assessing on the coordination mode and bonding in heteronuclear group‐13 dimetallocene. Issue 3 (30th August 2017) - Lu, Feifei; Yang, Lihua; Dang, Yaru; Li, Qingzhong; Li, Xiaoyan
Abstract: In this article, the coordination mode, the nature of metal–ligand interaction and dimetallic bonding in heteronuclear group‐13 dimetallocene (CpMM′CpI2 ; Cp = C5 H5, M/M′=B, Al, Ga, In, and Tl) have been investigated within the framework of the atoms in molecules theory, electron localization function, and energy decomposition analysis. The calculated results show that the symmetries of the title compounds, the coordination modes between the metal and ligand, the strength and nature of M‐ligand interaction and MM′ bond are well correlated with the periodicity changing of group‐13 metal atom going from the lighter to the heavier (B, Al, Ga, In, and Tl). The heavier group 13 metal atom is corresponding to the higher symmetry, stronger metal–ligand interaction, and weaker dimetallic bond. The covalent characters of both metal–ligand interaction and dimetallic bond are decreasing in the sequence of M′=Al, Ga, In, and Tl, for the same M atom. Abstract : DFT calculations reveal that the symmetries of the heteronuclear group‐13 dimetallocene, the coordination modes between the metal and ligand, and the nature of chemical bonds are well correlated with the periodicity changing of group‐13 metal atom going from lighter to heavier (In this order: B, Al, Ga, In, and Tl). The heavier of the group‐13 atom, the higher symmetry and higher coordination numbers the dimetallocene complex has.